Social Innovation as a tool in the transformation of an inclusive society. Accessibility and Social Innovation - Sampedro-Palacios, Cristina Belén; Pérez-Villar, Juana (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
Nowadays, talking about Accessibility is the same as talking about social inclusion, since transforming a society into an accessible society is making it inclusive. Accessibility has evolved over time, producing in it the changes that were taking place with society. Traditionally, it has been associated with the elimination of architectural barriers, but at present Universal Accessibility goes beyond the so-called physical accessibility. Contemplating a variety of subjects that encompasses many types of accessibility in many areas of a person’s life. From this study we try to review the evolution of Accessibility from its origins to the present trying to know its characteristics. Then we can link it with Social Innovation as an ally, with the aim of achieving an inclusive society accessible to all people, in which the diversity that characterizes human beings is an added value. All this through Social Work as a precursor of Social Welfare.